Exercise-induced Gastrointestinal Syndrome in Triathletes – a Systematic Review - Widawski, Michał; Górniak, Aleksandra; Kubas, Aleksandra; Rusiecka, Amelia; Sobczyk, Aleksander; Gizińska, Natalia; Lewandowska, Paulina (Quality in Sport, 2025)
Introduction and Purpose In recent decades, there has been a significant increase in interest in triathlon among amateur athletes. Despite the undeniable health benefits, participating in such a demanding discipline also carries numerous issues, such as injuries and gastrointestinal disorders. According to some studies, as many as 93% of individuals competing in triathlon events report symptoms such as nausea, abdominal pain, or diarrhea during exertion. This paper is devoted to examining these issues. Aim of the study We have discussed the most important pathophysiological mechanisms that lead to them, such as splanchnic ischemia, damage to the intestinal epithelium, and increased permeability of intercellular junctions in the intestines. Methods The following paper analyzed studies found on PubMed using keywords such as “exercise-induced gastrointestinal syndrome”, “gastrointestinal disorder in triathlon”, “EIGS management”, and “triathlon”. Articles include randomized controlled trials, meta-analyses, and systematic reviews published from 1990 to the present day, prioritizing resources published after 2020. Keywords exercise-induced gastrointestinal syndrome, gastrointestinal disorder in triathlon, EIGS management, triathlon Conclusions Unfortunately, despite numerous studies being conducted, there are still no sufficiently effective methods to prevent these ailments. According to current data, the most effective measures include reduced fiber intake in the pre-competition period and gut training to prepare them for such exertion.